Ответ:
...........................................
Объяснение:
1.
2.
3.
4.
5.
6.
7.
8.
9.
10.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
...........................................
Ответ:
Объяснение:
1.![\frac{b^{3} }{a^{2} } *\frac{a^{4} }{b^{5} } =\frac{a^{2} }{b^{2} } \frac{b^{3} }{a^{2} } *\frac{a^{4} }{b^{5} } =\frac{a^{2} }{b^{2} }](https://tex.z-dn.net/?f=%5Cfrac%7Bb%5E%7B3%7D%20%7D%7Ba%5E%7B2%7D%20%7D%20%2A%5Cfrac%7Ba%5E%7B4%7D%20%7D%7Bb%5E%7B5%7D%20%7D%20%3D%5Cfrac%7Ba%5E%7B2%7D%20%7D%7Bb%5E%7B2%7D%20%7D)
2.![\frac{x-y}{8-a} *\frac{8-a}{x+y}=\frac{x-y}{x+y} \frac{x-y}{8-a} *\frac{8-a}{x+y}=\frac{x-y}{x+y}](https://tex.z-dn.net/?f=%5Cfrac%7Bx-y%7D%7B8-a%7D%20%2A%5Cfrac%7B8-a%7D%7Bx%2By%7D%3D%5Cfrac%7Bx-y%7D%7Bx%2By%7D)
3.![\frac{a-b}{4c}/\frac{a-b}{16c^{2} } =\frac{a-b}{4c}*\frac{16c^{2}}{a-b} =4c \frac{a-b}{4c}/\frac{a-b}{16c^{2} } =\frac{a-b}{4c}*\frac{16c^{2}}{a-b} =4c](https://tex.z-dn.net/?f=%5Cfrac%7Ba-b%7D%7B4c%7D%2F%5Cfrac%7Ba-b%7D%7B16c%5E%7B2%7D%20%7D%20%20%3D%5Cfrac%7Ba-b%7D%7B4c%7D%2A%5Cfrac%7B16c%5E%7B2%7D%7D%7Ba-b%7D%20%3D4c)
4.![\frac{8x}{x^{2}-y^{2} } /\frac{4x}{x-y}=\frac{8x}{x^{2}-y^{2} } *\frac{x-y}{4x} =\frac{2}{(x-y)(x+y) } *\frac{x-y}{1} =\frac{2}{x+y} \frac{8x}{x^{2}-y^{2} } /\frac{4x}{x-y}=\frac{8x}{x^{2}-y^{2} } *\frac{x-y}{4x} =\frac{2}{(x-y)(x+y) } *\frac{x-y}{1} =\frac{2}{x+y}](https://tex.z-dn.net/?f=%5Cfrac%7B8x%7D%7Bx%5E%7B2%7D-y%5E%7B2%7D%20%20%7D%20%2F%5Cfrac%7B4x%7D%7Bx-y%7D%3D%5Cfrac%7B8x%7D%7Bx%5E%7B2%7D-y%5E%7B2%7D%20%20%7D%20%2A%5Cfrac%7Bx-y%7D%7B4x%7D%20%3D%5Cfrac%7B2%7D%7B%28x-y%29%28x%2By%29%20%7D%20%2A%5Cfrac%7Bx-y%7D%7B1%7D%20%3D%5Cfrac%7B2%7D%7Bx%2By%7D)
5.![\frac{16x^{2}y }{7z} *\frac{21z^{2} }{10xy^{2} } =\frac{8x }{1} *\frac{3z }{5y}=\frac{24xz}{5y} \frac{16x^{2}y }{7z} *\frac{21z^{2} }{10xy^{2} } =\frac{8x }{1} *\frac{3z }{5y}=\frac{24xz}{5y}](https://tex.z-dn.net/?f=%5Cfrac%7B16x%5E%7B2%7Dy%20%7D%7B7z%7D%20%2A%5Cfrac%7B21z%5E%7B2%7D%20%7D%7B10xy%5E%7B2%7D%20%7D%20%3D%5Cfrac%7B8x%20%7D%7B1%7D%20%2A%5Cfrac%7B3z%20%7D%7B5y%7D%3D%5Cfrac%7B24xz%7D%7B5y%7D)
6.![\frac{23mn^{2} }{5a^{3} }/\frac{46m^{3}n }{15a} =\frac{23mn^{2} }{5a^{3} }*\frac{15a}{46m^{3}n}=\frac{23mn^{2} *15a}{5a^{3} *46m^{3}n}=\frac{n *3}{a^{2} *2m^{2}}=\frac{3n}{2a^{2}m^{2}} \frac{23mn^{2} }{5a^{3} }/\frac{46m^{3}n }{15a} =\frac{23mn^{2} }{5a^{3} }*\frac{15a}{46m^{3}n}=\frac{23mn^{2} *15a}{5a^{3} *46m^{3}n}=\frac{n *3}{a^{2} *2m^{2}}=\frac{3n}{2a^{2}m^{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B23mn%5E%7B2%7D%20%7D%7B5a%5E%7B3%7D%20%7D%2F%5Cfrac%7B46m%5E%7B3%7Dn%20%7D%7B15a%7D%20%3D%5Cfrac%7B23mn%5E%7B2%7D%20%7D%7B5a%5E%7B3%7D%20%7D%2A%5Cfrac%7B15a%7D%7B46m%5E%7B3%7Dn%7D%3D%5Cfrac%7B23mn%5E%7B2%7D%20%2A15a%7D%7B5a%5E%7B3%7D%20%2A46m%5E%7B3%7Dn%7D%3D%5Cfrac%7Bn%20%2A3%7D%7Ba%5E%7B2%7D%20%2A2m%5E%7B2%7D%7D%3D%5Cfrac%7B3n%7D%7B2a%5E%7B2%7Dm%5E%7B2%7D%7D)
7.![\frac{5a}{a^{2}- b^{2} } /\frac{15a^{2} }{a-b} =\frac{5a*(a-b)}{15a^{2}(a-b)(a+b)}= \frac{1}{3a(a+b)}= \frac{1}{3a^{2} +3ab} \frac{5a}{a^{2}- b^{2} } /\frac{15a^{2} }{a-b} =\frac{5a*(a-b)}{15a^{2}(a-b)(a+b)}= \frac{1}{3a(a+b)}= \frac{1}{3a^{2} +3ab}](https://tex.z-dn.net/?f=%5Cfrac%7B5a%7D%7Ba%5E%7B2%7D-%20b%5E%7B2%7D%20%7D%20%2F%5Cfrac%7B15a%5E%7B2%7D%20%7D%7Ba-b%7D%20%3D%5Cfrac%7B5a%2A%28a-b%29%7D%7B15a%5E%7B2%7D%28a-b%29%28a%2Bb%29%7D%3D%20%5Cfrac%7B1%7D%7B3a%28a%2Bb%29%7D%3D%20%5Cfrac%7B1%7D%7B3a%5E%7B2%7D%20%2B3ab%7D)
8.![\frac{m+n}{3b} *\frac{9b^{2} }{m^{2} -n^{2} } =\frac{9b^{2}*(m+n)}{3b*(m+n)(m-n)}=\frac{3b}{m-n} \frac{m+n}{3b} *\frac{9b^{2} }{m^{2} -n^{2} } =\frac{9b^{2}*(m+n)}{3b*(m+n)(m-n)}=\frac{3b}{m-n}](https://tex.z-dn.net/?f=%5Cfrac%7Bm%2Bn%7D%7B3b%7D%20%2A%5Cfrac%7B9b%5E%7B2%7D%20%7D%7Bm%5E%7B2%7D%20-n%5E%7B2%7D%20%7D%20%3D%5Cfrac%7B9b%5E%7B2%7D%2A%28m%2Bn%29%7D%7B3b%2A%28m%2Bn%29%28m-n%29%7D%3D%5Cfrac%7B3b%7D%7Bm-n%7D)
9.![\frac{mx^{2} -my^{2} }{2m+8} *\frac{3m+12}{my+mx}= \frac{(mx+my)(x-y)*3(m+4)}{2*(m+4)(my+mx)}= \frac{(x-y)*3}{2}= \frac{3x-3y}{2} \frac{mx^{2} -my^{2} }{2m+8} *\frac{3m+12}{my+mx}= \frac{(mx+my)(x-y)*3(m+4)}{2*(m+4)(my+mx)}= \frac{(x-y)*3}{2}= \frac{3x-3y}{2}](https://tex.z-dn.net/?f=%5Cfrac%7Bmx%5E%7B2%7D%20-my%5E%7B2%7D%20%7D%7B2m%2B8%7D%20%2A%5Cfrac%7B3m%2B12%7D%7Bmy%2Bmx%7D%3D%20%5Cfrac%7B%28mx%2Bmy%29%28x-y%29%2A3%28m%2B4%29%7D%7B2%2A%28m%2B4%29%28my%2Bmx%29%7D%3D%20%5Cfrac%7B%28x-y%29%2A3%7D%7B2%7D%3D%20%5Cfrac%7B3x-3y%7D%7B2%7D)
10.![\frac{a^{2}-49 }{a^{2}+2ab+b^{2}} /\frac{a-7}{a+b}= \frac{(a+7)(a-7)(a+b) }{(a+b)(a+b)(a-7)}= \frac{a+7}{a+b} \frac{a^{2}-49 }{a^{2}+2ab+b^{2}} /\frac{a-7}{a+b}= \frac{(a+7)(a-7)(a+b) }{(a+b)(a+b)(a-7)}= \frac{a+7}{a+b}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%5E%7B2%7D-49%20%7D%7Ba%5E%7B2%7D%2B2ab%2Bb%5E%7B2%7D%7D%20%2F%5Cfrac%7Ba-7%7D%7Ba%2Bb%7D%3D%20%5Cfrac%7B%28a%2B7%29%28a-7%29%28a%2Bb%29%20%7D%7B%28a%2Bb%29%28a%2Bb%29%28a-7%29%7D%3D%20%5Cfrac%7Ba%2B7%7D%7Ba%2Bb%7D)